Factorization of matrices of permutation type - Kruglov, V. E. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
By using the methods of the theory of algebraic functions, we present an explicit construction of the canonical factorization of matrices of permutation type given on an open contour.